Development of Digital Fiqh Books to Improve Learning Outcomes SMP IT As-Sunnah Makassar - Sulfah Muhtar; P. Pattaufi; Farida Febriati; Nurhikmah H (Inovasi Kurikulum)
Rapid advances greatly influence the world of education in technology, information, and communication. Teachers must be able to use technology to create innovative and effective learning. This research aims to identify the need for digital books, design the development of digital books, and measure the validity, practicality, and effectiveness of digital books. This research uses research and development methods focused on developing digital books. The development model refers to the ADDIE development model with five stages: analysis, design, development, implementation, and evaluation. The research was conducted at SMP IT As-Sunnah Makassar with 30 research students, 1 Fiqh subject teacher, and two validators. The digital book developed was declared very valid by media content/design experts and valid by material experts. The level of practicality was measured from questionnaire responses by teachers and students. Both assessments stated that it was convenient. The level of effectiveness of digital books is measured by pretest and posttest, which shows an increase in learning outcomes and that they are declared very effective. Based on the analysis results, it can be concluded that the development of digital fiqh books can be used in the learning process.